Transitioning to Sustainable Industry, Innovation and Infrastructure - Wojciech Cynarski; Bożena Gajdzik (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We would like to invite you to contribute to an edited volume devoted to "Transitioning to Sustainable Industry, Innovation and Infrastructure". We believe that this should be a systemic issue, taking into account the contexts of social ecology and the environment (Cynical, 2014; Eiglad, 2015). New urban and industrial infrastructure and innovation in this area should take into account new urban plans for the creation of human-friendly spaces and smart cities (Azkuna, 2012) and the impact of the development of tourism on the changes of this space and great sporting and cultural events (Sieber and Cynarski 2010; Edizel and Ward 2016). Facilities for people with disabilities are included in the infrastructure that is being built. Innovations are being made regarding the materials used and savings including waste management, energy savings (preference for green energy) and other resources used in economies and industries (Wolniak et al., 2020; Piątkowski, Gajdzik and Mesjasz, 2020). In the past, sustainability was the doctrine of economics, which assumes a quality of life at the level allowed by the current development of civilization. The idea of sustainable development is summarized in the first sentence of the WCED—Our Common Future report: "At the current level of civilization, sustainable development is possible, that is, a development in which the needs of the present generation can be met without diminishing the chances of future generations meeting them" (Brundtland, 1987). A sustainable economy (including industry) should balance economic growth, environmental protection, quality of life and human health. It is not only about the natural environment, but also the artificial—i.e., man-made (as in Chicago School's work on human ecology). The doctrine of sustainable development strives for social justice by using environmental projects for higher efficiency. It is important to work and life now but needs to factor in future generations and their heritage, both cultural and natural (cf. Kozlowski 2000, 2007; Caradonna 2014; Alhaddi 2015). The priority is to set ecological standards for preserving the homeostasis of the ecosystem. Modern business is becoming more and more digital and intelligent. Enterprises implement new technologies of the fourth industrial revolution in the sustainable environment. Sustainable Industry 4.0 is a new concept for discussion by scientists and business (Gajdzik, B. et al., 2020). This concept has been gaining more and more interest among scientists and practitioners in recent years because there is more and more information about Industry 4.0 (Kagermann et al., 2011). Factories are becoming smarter, more efficient, safer and more environmentally friendly by linking and integrating production technologies and devices, information and communication systems, data and services in network infrastructures (Saniuk et al., 2020). New business models with cyber-physical systems (CPSs) are being built (Lee, et al., 2015; Gajdzik, Chapter 3 in: Scalability and Sustainability, 2020) but sustainability must not be forgotten in these models. Transitioning to Sustainable Industry, Innovation and Infrastructure is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. The book series is intended to reach beyond disciplinary, even academic boundaries.
Keywords: 330; infrastructure; innovation for sustainability; sustainable Industry